Dual Effects of Lipid Metabolism on Osteoblast Function - Alekos, Nathalie S.; Moorer, Megan C.; Riddle, Ryan C. (Frontiers in Endocrinology, 2020)
The skeleton is a dynamic and metabolically active organ with the capacity to influence whole body metabolism. This newly recognized function has propagated interest in the connection between bone health and metabolic dysfunction. Osteoblasts, the specialized mesenchymal cells responsible for the production of bone matrix and mineralization, rely on multiple fuel sources. The utilization of glucose by osteoblasts has long been a focus of research, however, lipids and their derivatives, are increasingly recognized as a vital energy source. Osteoblasts possess the necessary receptors and catabolic enzymes for internalization and utilization of circulating lipids. Disruption of these processes can impair osteoblast function, resulting in skeletal deficits while simultaneously altering whole body lipid homeostasis. This article provides an overview of the metabolism of postprandial and stored lipids and the osteoblast’s ability to acquire and utilize these molecules. We focus on the requirement for fatty acid oxidation and the pathways regulating this function as well as the negative impact of dyslipidemia on the osteoblast and skeletal health. These findings provide key insights into the nuances of lipid metabolism in influencing skeletal homeostasis which are critical to appreciate the extent of the osteoblast’s role in metabolic homeostasis.